Solve for t s=ut+1/(2at^2)

Math
s=ut+12at2
Rewrite the equation as ut+12at2=s.
ut+12at2=s
Find the LCD of the terms in the equation.
Tap for more steps…
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
1,2at2,1
Since 1,2at2,1 contain both numbers and variables, there are two steps to find the LCM. Find LCM for the numeric part 1,2,1 then find LCM for the variable part a1,t2.
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
Since 2 has no factors besides 1 and 2.
2 is a prime number
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
The LCM of 1,2,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.
2
The factor for a1 is a itself.
a1=a
a occurs 1 time.
The factors for t2 are t⋅t, which is t multiplied by each other 2 times.
t2=t⋅t
t occurs 2 times.
The LCM of a1,t2 is the result of multiplying all prime factors the greatest number of times they occur in either term.
a⋅t⋅t
Multiply t by t by adding the exponents.
Tap for more steps…
Move t.
a⋅(t⋅t)
Multiply t by t.
a⋅t2
at2
The LCM for 1,2at2,1 is the numeric part 2 multiplied by the variable part.
2at2
2at2
Multiply each term by 2at2 and simplify.
Tap for more steps…
Multiply each term in ut+12at2=s by 2at2 in order to remove all the denominators from the equation.
ut⋅(2at2)+12at2⋅(2at2)=s⋅(2at2)
Simplify each term.
Tap for more steps…
Rewrite using the commutative property of multiplication.
2(ut)(at2)+12at2⋅(2at2)=s⋅(2at2)
Multiply t by t2 by adding the exponents.
Tap for more steps…
Move t2.
2(u(t2t))a+12at2⋅(2at2)=s⋅(2at2)
Multiply t2 by t.
Tap for more steps…
Raise t to the power of 1.
2(u(t2t1))a+12at2⋅(2at2)=s⋅(2at2)
Use the power rule aman=am+n to combine exponents.
2(ut2+1)a+12at2⋅(2at2)=s⋅(2at2)
2(ut2+1)a+12at2⋅(2at2)=s⋅(2at2)
Add 2 and 1.
2(ut3)a+12at2⋅(2at2)=s⋅(2at2)
2(ut3)a+12at2⋅(2at2)=s⋅(2at2)
Rewrite using the commutative property of multiplication.
2ut3a+212at2(at2)=s⋅(2at2)
Cancel the common factor of 2.
Tap for more steps…
Factor 2 out of 2at2.
2ut3a+212(at2)(at2)=s⋅(2at2)
Cancel the common factor.
2ut3a+212(at2)(at2)=s⋅(2at2)
Rewrite the expression.
2ut3a+1at2(at2)=s⋅(2at2)
2ut3a+1at2(at2)=s⋅(2at2)
Cancel the common factor of at2.
Tap for more steps…
Cancel the common factor.
2ut3a+1at2(at2)=s⋅(2at2)
Rewrite the expression.
2ut3a+1=s⋅(2at2)
2ut3a+1=s⋅(2at2)
2ut3a+1=s⋅(2at2)
Rewrite using the commutative property of multiplication.
2ut3a+1=2sat2
2ut3a+1=2sat2
Solve for t s=ut+1/(2at^2)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top